Human Right, PSK And Justice In Law - Octarina, Nynda Fatmawati; Muh. Barid Nizarudin Wajdi (STAI Miftahul Ula Nganjuk, 2024)
Human rights is an international issue and a highly prominent source of conversation in the current decade. This requires serious attention for its enormous dimensions of its influence in international and national life. The state of Indonesia as a state of law (rechtstaat) also needs to be understood higher attention to human rights. Therefore, that in reform era, a big agenda requires a change of life order in nation and state. One of the most notable changes is the protection of citizen rights related to Human Rights itself. Journalist as journalistic perpetrator can be categorized as a witness or victim if the condition fulfills the requirement as witness or victim as mentioned in Law of Witness and Victim Protection, Criminal Code. Victim means journalist is suffering from physical, mental, and/or economic loss caused by criminal act and as a witness if the reporter hears on his own behalf and personally experiences a criminal act. As a witness and victim, journalist is also entitled to the protection of the law granted by the state as in Witness and Victim Protection Act. These rights ensure safety and security of witnesses and victims to assist smoothness in a criminal proceeding process.